Kend dig selv: Om det sociale individ og det sunde samfund - Birkelund, Regner (Grundtvig-Studier, 2005)
Kend dig selv: Om det sociale individ og det sunde samfund [Know yourself: On the social individual and the healthy society] By Regner Birkelund On the basis of a speech Gr held at Marielyst Highschool in 1862, the significance of the ancient Greek ideal of enlightenment, embodied in the Latin maxim Nosce te ipsum [Know yourself], is explored, which can be taken back to the Oracle at Delphi but which was also a central turning-point in both Plato’s and Aristotle’s pedagogic and social thinking. Partly by introducing the Greek ideal of enlightenment into his speech, Gr reveals a Greek dimension to his ideas on lifeenlightenment and social communality which has hitherto been only sporadically focussed upon in Grundtvig scholarship. This perception, that the expression ‘Know yourself simultaneously refers itself to an act of cognition and to the development of an innate potential for ethical engagement, is substantiated and placed in relationship to Gr’s concept of the divine image in humanity.